Bibehållen lön eller bristande ersättning? - Den systematiska konflikten mellan svensk reglering av graviditetspenning och EU-rättens krav på skälig ersättning vid arbetsförbud av gravida - Ahlgren,Rebecca; Månhardt,Rebecca (2026)
The purpose of the thesis is to analyze and problematize how the Swedish regulation of economic compensation for pregnant employees during work prohibition doesn’t fulfill the requirements of maintaining salary or adequate allowance according to the Maternity protection directive 92/85/EEC. The thesis uses the legal dogmatic methodology with socio-legal and critical aspects to address the research question. Pregnant women prohibited to work due to risks in the working environment are entitled to pregnancy benefits in Sweden. This benefit is provided through the social insurance system and provides about 80 percent of her salary up to a maximum income. This economic compensation is lower than what the directive grants according to AD 2025 no. 57. EU case law determines that article 11.1 of the directive has direct effect, requiring the Swedish labour court to ensure women’s rights despite national legislation. This issue is caused by the system’s overall construction which systematically discriminates against pregnant women. In summary, the regulation of economic compensation during pregnancy is a complex area. Pregnant women’s right to compensation depends on decisions by others, risking legal gaps. A legal reform is needed to fully ensure pregnant women's right to economic compensation during work prohibition.
Keywords: mödraskyddsdirektivet 92/85/EEG; skälig ersättning; graviditetspenning; diskriminering.